Pierwszy szczebel - Tołstoj, Lew Nikołajewicz; Ojcewicz, Grzegorz (Zoophilologica. Polish Journal of Animal Studies, 2024)
Leo Tolstoy’s essay, The First Step (Первая ступень) written in 1891, is a multi-dimensional text whose purpose was not only to try to convert people to the righteous path of living through consistently followed restraint and self-control over one’s desires, but its author also encouraged people – in a rather convincing way – to become vegetarians. Tolstoy claimed that meat-free diet closely relates to healthy nutrition and considerably limits or even eliminates the suffering of animals being slaughtered on a mass scale for consumption in pain and death factories, as he referred to mechanised slaughterhouses. Using naturalistic images, the writer describes horrifying scenes he witnessed at the abattoir in Tula. The text is filled with drastic imagery, sounds and foul odours wafting from the slaughterhouse and the vision of inhumane practices of butchers, young and old, devoid of any sympathy towards the animals being killed. In hindsight it must be regretfully noted that Tolstoy’s essay has not changed people’s dietary habits and vegetarianism has not managed to supplant the traditional, mostly meat-based menu.